2017
DOI: 10.1136/bmjopen-2017-017465
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profiles and determinants of total cholesterol and hypercholesterolaemia among 25–74 year-old urban and rural citizens of the Yangon Region, Myanmar: a cross-sectional study

Abstract: ObjectiveThe first is to estimate the prevalence of dyslipidaemia (hypercholesterolaemia, hypertriglyceridaemia, high low-density lipoprotein (LDL) level and low high-density lipoprotein (HDL) level), as well as the mean levels of total cholesterol, triglyceride, LDL and HDL, in the urban and rural Yangon Region, Myanmar. The second is to investigate the association between urban-rural location and total cholesterol.DesignTwo cross-sectional studies using the WHO STEPS methodology.SettingBoth the urban and rur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
(16 reference statements)
3
15
0
2
Order By: Relevance
“…The participants were sampled to reflect the general population of Yangon. In a 2014 study in Yangon, the age-standardized prevalences of hypertension and hypercholesterolemia were previously reported to be 34.6% and 46.8%, respectively, while the prevalences of diabetes were reported to be 12.1% (urban population) and 7.1% (rural population) [ 17 , 18 , 19 ]. The consumption pattern of oils in the Yangon region was comparable in both survey years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The participants were sampled to reflect the general population of Yangon. In a 2014 study in Yangon, the age-standardized prevalences of hypertension and hypercholesterolemia were previously reported to be 34.6% and 46.8%, respectively, while the prevalences of diabetes were reported to be 12.1% (urban population) and 7.1% (rural population) [ 17 , 18 , 19 ]. The consumption pattern of oils in the Yangon region was comparable in both survey years.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with our findings that palm oil was most commonly used by participants with low educational level and income, among rural dwellers and among women. More than half of the population of Yangon (54%) has an income of <1.90 USD/per day [ 19 ], which may explain the widespread use of palm oil. A study of the consumer preference for vegetable oil in Myanmar in 2011 showed that peanut oil was rated highly regarding taste, aroma, nutrition status, and health benefits; however, it had low affordability [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 6 ] Hypercholesterolemia has resulted in 4 million deaths and a disability-adjusted life loss of up to 88.7 million people globally. [ 7 ] Through multiple studies of risk analysis of CHD angina pectoris, HTN is generally regarded as an important risk factor for CHD angina pectoris. [ 8 ] Combined with Gensini scoring system, Coronary angiography (CAG) makes a precise diagnosis of the number, location, scope, and vascular wall of coronary artery stenosis (CAS), [ 9 ] CAG is regarded as the best way to diagnose CHD and the most powerful method of evaluating the degree of CAS.…”
Section: Introductionmentioning
confidence: 99%